2017
DOI: 10.1016/j.compositesa.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Bridging mechanisms of through-thickness reinforcement in dynamic mode I&II delamination

Abstract: Z-pin through-thickness reinforcement is used to improve the impact resistance of composite structures; however, the effect of loading rate on Z-pin behaviour is not well understood. The dynamic response of Z-pins in mode I and II delamination of quasiisotropic IM7/8552 laminates was characterized experimentally in this work. Z-pinned samples were loaded at both quasi-static and dynamic rates, up to a separation velocity of 12m/s. The efficiency of Z-pins in mode I delamination decreased with loading rate, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…The response of Z-pins in mixed mode delamination has been characterized at quasi-static loading rates, and shows a transition of failure mode from pull-out to rupture as the mixed mode ratio increases [14,21]. The high rate tests presented in [17] clearly showed the extremes of different behaviour under pure mode I and mode II loading, and showed that in particular the mode I behaviour was affected by the rate of loading. These tests [17] did not however cover the high rate behaviour of mixed mode cases in between the pure mode cases, which are more likely to be encountered in realistic loading of engineering structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of Z-pins in mixed mode delamination has been characterized at quasi-static loading rates, and shows a transition of failure mode from pull-out to rupture as the mixed mode ratio increases [14,21]. The high rate tests presented in [17] clearly showed the extremes of different behaviour under pure mode I and mode II loading, and showed that in particular the mode I behaviour was affected by the rate of loading. These tests [17] did not however cover the high rate behaviour of mixed mode cases in between the pure mode cases, which are more likely to be encountered in realistic loading of engineering structures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is difficult to quantify the local loading rate near the Z-pin, as it may change significantly depending on the stability of the crack propagation. Cui et al have thus developed a testing protocol that is suitable for us in a Hopkinson bar apparatus and is able to extract the rate dependent bridging response of an individual pin [17]. This was an evolution of the single pin test that has been used quasi-statically [9,14,18,19], and was applied to pure mode I and pure mode II loading.…”
Section: Introductionmentioning
confidence: 99%
“…Difference in failure modes of Z-pins and the epoxy pockets, was responsible for the change in Z-pin influence. The in-plane failure mechanisms of Zpinned laminates is very complicated and its evolution with strain rate involves many issues including the rate and pressure dependent plasticity of laminate matrix, as well as the complex failure of Z-pins which is also loading rate dependent [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Z-pinning has been one of the most popular solutions of TTR; where metallic or carbon fibre rods are inserted through the laminate thickness for resisting the growth of delamination [7]. Z-pinning significantly increases the resistance against the inter-laminar crack propagation [8][9][10][11] and has recently been found to be effective in improving the dynamic delamination toughness, although its efficiency decreases with loading rate [12,13]. The outof-plane performance improvement comes at a cost of the in-plane performance, which will see reduction in strength due to the defects caused by the Z-pinning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation